Acaricidal activity of cashew nut shell liquid associated with essential oils from Cordia verbenacea and Psidium guajava on Rhipicephalus microplus. Issue 4 (4th July 2019) - De Carvalho Castro, Karina Neoob; Costa-Júnior, Lívio Martins; Lima, David Fernandes; Canuto, Kirley Marques; Sousa De Brito, Edy; De Andrade, Ivanilza Moreira; Teodoro, Mauro Sérgio; Oiram-Filho, Francisco; Dos Santos, Raimunda Cardoso; Mayo, Simon Joseph
ABSTRACT: The aim of this study was to assess the effectiveness of cashew nut shell liquid (CNSL), Cordia verbenacea and Psidium guajava, both alone and in association against Rhipicephalus microplus . Larval packet and adult immersion tests were conducted in concentrations ranging from 3.1 at 100.0mg mL −1 . CNSL was effective against engorged females (99.6%) at 100.0mg mL −1 and against larvae (99.2 %) at 50.0mg mL −1 . The highest efficacy on engorged females was achieved by the essential oils of P. guajava at 12.5mg mL −1 (99.9%), followed by those of C. verbenacea at 25.0mg mL −1 (96.9%), while a low larvicidal activity of 5.8 and 59.0% was, respectively, obtained. The association at 50.0mg mL −1 had asignificant effect on both life stages of R. microplus . This association caused considerable larval mortality (95.3%) and high efficacy on engorged females (93.9%).